Demand for fisheries products in Brazil (Scientia Agricola, 2012)
Fish consumption per capita in Brazil is relatively modest when compared to other animal proteins. This study analyses the influence of protein prices, other food prices and population income on the fish demand in Brazil. First, the problem of fish supply in Brazil is characterized. It is followed by reviews of the relevant economic theory and methods of Almost Ideal Demand System - AIDS and their elasticity calculations. A descriptive analysis of fish demand in Brazil using the microdata called "Pesquisa de Orçamento Familiar" (Familiar Budget Research) - POF 2002-2003 is presented. Finally, demand functions and their elasticities are calculated for two different cases: one considering five groups of animal proteins (Chicken; Milk and Eggs; Fish; Processed Proteins and Red Meat) and other with seven groups of food categories (Cereals; Vegetables and Fruits; Milky and Eggs; Oils and Condiments; Fish; Other processed foods; and Meats). The main results are: per capita consumption of fish (4.6 kg per inhabitant per year) is low in Brazil because few households consume fish. When only households with fish consumption are considered, the per capita consumption would be higher: 27.2 kg per inhabitant per year. The fish consumption in the North-East Region is concentrated in the low-income class. In the Center-South Region, the fish consumption is lower and concentrated in the intermediate income classes. The main substitutes for fish are the processed proteins and not the traditional types of meat, such as chicken and red meat.